Research on Piezoelectric Energy harvesting from Multi-Direction Wind-Induced Vibrations. Issue 1 (December 2020) - Chen, Yuansheng; Gu, Cong; Zhao, Pengcheng; Chen, Wei
Abstract: Micro electric devices have been widely applied in outdoor field work, but the battery power limits its performance. Piezoelectric energy harvesting from wind-induced vibration is an attractive power solution for the micro electric devices in field work. Its output characteristics of proposed system is analysed under different wind speed and direction. Experimental results show that the proposed system can harvest more energy if the incoming flow is parallel to the piezoelectric plate. Its output voltage increases from 2.5V to 10.3V when the wind speed ranges from 9m/s to 21m/s. The output voltage can achieve 8.5V, if the flow direction is vertical to the piezoelectric plate. But the proposed harvesting system outputs very small voltage in case the flow direction from the top. These results show that the piezoelectric energy harvesting system can collect the wind energy from multi-direction, and have potential application to power the micro electric devices.